Asymmetrical Warfare and Peace Building in Afghanistan: An Appraisal (Khairulummah, 2023)
The concept of asymmetrical warfare has a chequered history. In primitive ages, the tools of warfare were simple and less devastative. In modern warfare especially in post-World War 2, nuclear weapons, biological weapons and chemical weapons replaced general armoured which can wipe out human beings from earth in no time. In such circumstances, the weaker nations like Afghanistan prompt to choose guerrilla techniques against United States of America and its allies under the ambit of North Atlantic Treaty Organisation (NATO). America and world community mishandled the Afghan crisis and ignored the decades inherited guerrilla training of Afghan people and its forces and warfare history against the invaders in different times; they only used naked weapons rather than to open diplomatic channels to bring peace in war-torn Afghanistan.
Keywords: Asymmetrical, Warfare, Peace, Afghanistan